2019
DOI: 10.1002/mrc.4844
|View full text |Cite
|
Sign up to set email alerts
|

1H–13C HMBC NMR experiments as a structural and analytical tool for the characterization of elusive trans/cis hydroperoxide isomers from oxidized unsaturated fatty acids in solution

Abstract: The radical‐dependent oxidation of unsaturated fatty acids is a fundamental reaction in lipid chemistry, biochemistry, and technology. We report herein the first successful application of 1H–13C HMBC NMR experiment for the identification and quantification of complex and minor (3.9% to 0.85%) components of cis and trans primary hydroperoxide isomers of oxidized oleate and linoleate methyl esters in solution, without the need of laborious isolation of the individual components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…It can therefore be concluded that Δδ( 13 C) trans / cis ~ 5 to 6 ppm of the methine CH-O-O-H carbons can be of high diagnostic value for the identification of trans / cis geometric isomerism of hydroperoxides, contrary to 1 H chemical shifts of the hydroperoxide protons. Table 6 shows a very good agreement of the quantification data of Ahmed et al [ 137 ] with those of isolated hydroperoxides from the literature. Similarly, the 13 C chemical shifts of trans / cis hydroperoxides of methyl oleate, using the 1 H- 13 C HMBC experiments, were shown to be in excellent agreement with those obtained from the literature with the use of chromatographically isolated hydroperoxides ( Figure 39 ).…”
Section: Nmr Spectroscopy In Mixture Analysissupporting
confidence: 70%
See 1 more Smart Citation
“…It can therefore be concluded that Δδ( 13 C) trans / cis ~ 5 to 6 ppm of the methine CH-O-O-H carbons can be of high diagnostic value for the identification of trans / cis geometric isomerism of hydroperoxides, contrary to 1 H chemical shifts of the hydroperoxide protons. Table 6 shows a very good agreement of the quantification data of Ahmed et al [ 137 ] with those of isolated hydroperoxides from the literature. Similarly, the 13 C chemical shifts of trans / cis hydroperoxides of methyl oleate, using the 1 H- 13 C HMBC experiments, were shown to be in excellent agreement with those obtained from the literature with the use of chromatographically isolated hydroperoxides ( Figure 39 ).…”
Section: Nmr Spectroscopy In Mixture Analysissupporting
confidence: 70%
“…Sharp hydroperoxide-proton resonances have been reported in the case of oxidation of DHA ethyl ester [ 101 ] and conjugated linoleic-acid (CLA) methyl ester [ 136 ]; however, no attempt has been made to utilize the -OOH resonances as structural and analytical tools. Ahmed et al [ 137 ] achieved very sharp resonances Δν 1/2 ≤ 2.5 Hz, of the hydroperoxide protons in CDCl 3 of a sample of methyl oleate, which was oxidized in the presence of atmospheric oxygen in a breaker at 70 °C for 135 h. The excellent resolution of the C-O-O-H protons, without the use of CDCl 3 /DMSO- d 6 binary mixtures, was attributed to the absence of acidic groups, contrary to the case of the free fatty acids, which accelerate intermolecular proton transfer and thus result in linewidth broadening. Optimization of the 1 H- 13 C HMBC experiments for 3 J ( 13 C-O-O- 1 H) coupling of ~4 Hz resulted in two sets of 13 C connectivities at 86.7 and 81.1 ppm with excellent resolution and sensitivity ( Figure 38 ), despite the extremely low concentration of the hydroperoxides (3.9% to 0.8%).…”
Section: Nmr Spectroscopy In Mixture Analysismentioning
confidence: 99%
“…The present method of DFT calculations of 1 H-NMR chemicals shifts in parallel with the use of the computer assisted structure elucidation (CASE) program [ 46 , 47 ] and the development of experimental methods [ 6 , 10 , 48 ], could be of primary importance in geometric isomer identification and high resolution structural determination not only in isolated CLAs and their primary oxidation products [ 49 ], but also in mixture analysis in the emerging field of lipidomics [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…We report herein an extension of our previous study on the use of 1 H- 13 C HMBC NMR experiments as a structural and analytical tool for the identification and quantification of hydroperoxide isomers [ 26 , 27 ]. Complex hydroperoxides and endo -hydroperoxides of methyl linolenate were identified and quantified, with the combination of selective 1D TOCSY and 1 H- 13 C HMBC NMR techniques without laborious isolation of the individual components.…”
Section: Introductionmentioning
confidence: 99%